Extensão em manejo integrado de pragas (MIP) junto a produtores de hortaliças do Vale do Ribeira - Pavarini, Ronaldo [UNESP]; Aguiar, Michele Gonçalves de Almeida [UNESP]; Sakaguchi, Paula Hiroko [UNESP]; Demonari, Caio Guidetti [UNESP]; Ansante, Thiago Felipe [UNESP]; Sentinello, Edson Luiz de Almeida Baptista [UNESP]; Pavarini, Gláucia Maria Pereira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The Ribeira Valley territory in São Paulo consists of 23 municipalities and the region there are 9000 farms. Producers are responsible for agriculture, mostly small and medium presenting low technological level Thus, we see the need for activities that may turn this scenario in order to provide information and training to this farmer. The Integrated Pest Management is a system that aims to integrate pest control methods taking into account ecological, economic and social aspects. Thus this project aims to bring to the farmer's Ribeira Valley information about the MIP, which can help positively in the production system providing greater sustainability and establishment of this producer in the field. The service to farmers is done through ongoing activities involving theoretical and practical field. The course is taught on the farm to facilitate the mobilization and learning. For each course are formed groups of up to 20 to 25 farmers, thereby disseminate and apply the concepts of Integrated Pest Management. The project is implemented in the region since 2010 serving several municipalities as Registo, Juquiá and Miracatu, among others due to the demand that comes to the project coordinators. In this way we have been served 208 farmers mainly vegetables and can also participate producers of other crops depending on interest and availability. In addition, another aspect that has created strong demand from regional farmers is then diagnose technical guidance aimed at entomological problem solving related to agricultural crops in the area, this aspect routinely requested by producers and attended by the team responsible for the project, whereas this step is also part of learning about MIP by producers.

O território Vale do Ribeira em São Paulo é composto por 23 municípios e na região existem 9 mil propriedades rurais. Os produtores responsáveis pela atividade agrícola são, em sua maioria, pequenos e médios apresentando baixo nível tecnológico Assim, percebe-se a necessidade de atividades que venham transformar este cenário no sentido de fornecer informações e formação a este produtor rural. O Manejo Integrado de Pragas é um sistema que visa integrar métodos de controle de pragas levando em consideração aspectos ecológicos, econômicos e sociais. Desta maneira este projeto tem como objetivo levar até ao agricultor do Vale do Ribeira informações sobre o MIP, que possam auxiliar positivamente no sistema produtivo propiciando uma maior sustentabilidade e fixação deste produtor no campo. O atendimento ao produtor rural é feito por meio de curso envolvendo atividades teóricas e práticas de campo. O curso é ministrado na propriedade rural para facilitar a mobilização e aprendizado. Para cada mini-curso são formados grupos de no máximo 20 produtores rurais, conseguindo assim difundir e aplicar os conceitos de Manejo Integrado de Pragas. O projeto é executado na região desde 2010 atendendo vários municípios como Registro, Juquiá e Miracatu, dentre outros em função da demanda que chega até os coordenadores do projeto. Desta maneira já foram atendidos 208 produtores rurais principalmente de hortaliças, podendo participar também produtores de outras culturas em função do interesse e disponibilidade. Além disto, outro aspecto que tem criado forte demanda por parte dos produtores rurais regionais é a diagnose seguida de orientação técnica visando a solução de problemas entomológicos relacionados aos cultivos agrícolas da região, aspecto este rotineiramente requisitado pelos produtores e atendido pela equipe responsável pelo projeto, considerando que esta etapa também faz parte do aprendizado sobre MIP por parte dos produtores.
Keywords: Integrated pest management; MIP; Vale do Ribeira; Manejo integrado de pragas; MIP; Vale do Ribeira